Personality in Literature - Scott-James, R. A. (Rolfe Arnold), 1878- (Salt Lake City, UT : Project Gutenberg, 2007)
"Personality in Literature" by R. A. Scott-James is a critical examination of the role of personality in literary creation and appreciation, written in the early 20th century. The work explores the intersection of literature and art, the influence of modern life on literary creation, and the relationship between literature and individual personalities, particularly focusing on how personal experiences shape artistic expression. The book addresses significant literary figures and movements through a philosophical lens, presenting a nuanced understanding of literary aesthetics. The opening of the work sets the stage for a thorough discourse on aesthetic judgments, drawing the reader into a discussion on the concept of beauty in art and literature. Scott-James reflects on a personal experience at a Post-Impressionist art exhibition, illustrating the subjective nature of beauty and examining the various perspectives on what constitutes artistic merit. He critiques contemporary attitudes that dismiss beauty as an outdated concept while advocating for an appreciation of art as an end in itself, separate from utilitarian or ethical considerations. The text invites readers to explore these themes further, building a foundation for subsequent discussions on how personal ideals and societal trends influence the creation and evolution of literature. (This is an automatically generated summary.)
Release date is 2007-08-13
Jeannie Howse, David Clarke and the Distributed Proofreaders
Keywords: Literature; English literature -- 20th century -- History and criticism